(untitled) (The Macau Ricci Institute Journal, 2023)
Friendship is a key relationship in many cultures. (Lu et al, 2020) In this paper, I would like to present a single example of friendship in dire circumstances. The friendship described here occurred during the Japanese occupation of the Dutch East Indies (now Indonesia) when a group of young women were forced into sexual slavery by the Japanese military. The description here is part of a wider study of the spirituality of Jeanne Alida “Jan” Ruff-O’Herne, one of those young women. In the first part of the paper, I will provide a brief outline of her life, while the second part will provide some reflections on friendship, which I have drawn from her experience.